Placenta-derived mesenchymal stem cells protect against diabetic kidney disease by upregulating autophagy-mediated SIRT1/FOXO1 pathway - Honghong Liu; Jiao Wang; Guanru Yue; Jixiong Xu (Renal Failure)
Diabetic kidney disease (DKD) is a common chronic microvascular complication of diabetes mellitus. Although studies have indicated the therapeutic potential of mesenchymal stem cells (MSCs) for DKD, the underlying molecular mechanisms remain unclear. Herein, we explored the renoprotective effect of placenta-derived MSCs (P-MSCs) and the potential mechanism of SIRT1/FOXO1 pathway-mediated autophagy in DKD. The urine microalbumin/creatinine ratio was determined using ELISA, and renal pathological changes were detected by special staining techniques. Immunofluorescence was used for detecting the renal tissue expression of podocin and nephrin; immunohistochemistry for the renal expression of autophagy-related proteins (LC3, Beclin-1, SIRT1, and FOXO1); and western blotting and PCR for the expression of podocyte autophagy- and pathway-related indicators. We found that P-MSCs ameliorated renal tubular injury and glomerular mesangial matrix deposition and alleviated podocyte damage in DKD rats. PMSCs enhanced autophagy levels and increased SIRT1 and FOXO1 expression in DKD rat renal tissue, whereas the autophagy inhibitor 3-methyladenine significantly attenuated the renoprotective effect of P-MSCs. P-MSCs improved HG-induced Mouse podocyte clone5(MPC5)injury, increased podocyte autophagy, and upregulated SIRT1 and FOXO1 expression. Moreover, downregulation of SIRT1 expression blocked the P-MSC-mediated enhancement of podocyte autophagy and improvement of podocyte injury. Thus, P-MSCs can significantly improve renal damage and reduce podocyte injury in DKD rats by modulating the SIRT1/FOXO1 pathway and enhancing podocyte autophagy.